Inactivation of the Vitamin D Receptor in APC(min/+) Mice Reveals a Critical Role for the Vitamin D Receptor in Intestinal Tumor Growth - Zheng, Wei (2011)
Emerging evidence supports an inhibitory role for vitamin D in colorectal carcinogenesis, but the mechanism remains unclear. The APC/β-catenin pathway plays a critical role in colorectal carcinogenesis. The purpose is this study is to explore the interactions of vitamin D and APC/β-catenin pathways in intestinal tumor development. APC(min/+) mice with genetic inactivation of the vitamin D receptor (VDR) were generated through breeding. Intestinal tumorigenesis was compared between APC(min/+) and APC(min/+)VDR(−/−) mice at different ages. No differences were seen in the number of small intestinal and colonic tumors between APC(min/+) and APC(min/+)VDR(−/−) mice at 3, 4 and 6–7 months of age. The size of the tumors, however, was significantly increased in APC(min/+)VDR(−/−) mice in all age groups. Immunostaining showed a significant increases in β-catenin, cyclin D1, phosphorylated Stat-3 and MSH-2 levels and decreases in Stat-1 in APC(min/+)VDR(−/−) tumors compared to APC(min/+) tumors. These observations suggest that VDR signaling inhibits tumor growth rather than tumor initiation in the intestine. Thus, the increased tumor burden in APC(min/+)VDR(−/−) mice is likely due to the loss of the growth-inhibiting effect of VDR. This study provides strong evidence for the in vivo relevance of the interaction demonstrated in vitro between the vitamin D and β-catenin signaling pathways in intestinal tumorigenesis.